WAYS OF FORMATION AND DEVELOPMENT OF TEACHER'S READINESS TO THE INTRODUCTION OF INNOVATIVE TEACHING METHODS IN THE EDUCATIONAL PROCESS OF HIGHER EDUCATION INSTITUTIONS - Nataliia Naumenko; Svitlana Myronchenko; Andrіі Kozlov ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Today the teaching of the subjects should be related to the review of a number of organizational and pedagogical support of educational process in the framework of the transition from reproductive studying to pedagogy of cooperation. To this end, the teachers took part in the training "Innovative activities of the Teacher", which consisted of several mini-trainings. The aim of the training was to develop new professional skills in teachers; acquisition of new technologies in teaching practice; learning how to communicate effectively, how to react, and how to behave; the search for effective solutions to the problems identified; formation and development of communication skills among participants of the educational process; development of skills to apply various forms of organization and innovative teaching methods.